Cassava-Mealybug interactions - Paul-André Calatayud (IRD Éditions, 2006)
Most basic information on plant-mealybug interactions during the last decade has come from research on the cassava Manihot esculenta Crantz (Euphorbiaceae) system with two mealybug species, namely Phenacoccus manihoti Matile-Ferrero and Phenacoccus herreni Cox and Williams (Sternorrhyncha: Pseudococcidae). Both these insects cause severe damage to cassava in Africa and South America, respectively. This book reviews these interactions (plant selection by the insects, nutritional requirements, influence of the climate, intrinsic and extrinsic plant-defence mechanisms). It should be useful for entomologists, crop scientists, agronomists and ecologists as well as for teachers and students.